PROBLEMATIKA PENERAPAN LOGIKA POSITIVISTIK DALAM PENEGAKAN HUKUM PIDANA TERHADAP TUNTUTAN KEADILAN SUBSTANTIF - Umi Rozah (Masalah-Masalah Hukum, 2014)
In the criminal law enforcemet, criminal law agencies in the criminal justice process in every stages (investigation, prosecution and the court examination) tend to take positivism or legism thinking. In the logic of positivistic, they only recognized of content of the Act. In this way, they just enforce the legal certainty as the main of purpose. Here they just enforce of the legality principle as formulated in the Article 1 (1) Indonesian Penal Code. We need methods to crash of deadlock in the positivistic thinking in the criminal justice process to fulfill of substantive justice, especially, in the de minimis or insignificant cases. The cases which substance of contradiction of legal values about the legal certainty, the legal benefit and the legal justice. and inthe cases which involved of beyond of the law factors. The methods were needed to change the way of thinking/ conceptions / ideas of the criminal law agencies to interpret of every content of the Act by the hermeneutic method.